أثر مخاطر الائتمان على أداء البنوك التجارية في ضوء اتفاقية بازل 2: دراسة تطبيقية - محمد، آية ماهر; عبدالعال، محمود حامد; صبح، محمود محمد عبدالهادي (جامعة عين شمس - كلية التجارة, 2021)
هدف هذا البحث إلى معرفة تأثير مخاطر الائتمان (مقاسه برأس المال المطلوب لمواجهة مخاطر الائتمان وفق معايير بازل 2) على الأداء المالي للبنوك التجارية (مقاس بـ الربحية وجودة الأصول)، وذلك خلال سلسلة زمنية ربعية قدرها ثماني سنوات، تبدأ من الربع الأول لعام 2013 حتى الربع الرابع لعام 2020 لعينة تتكون من 7 بنوك من البنوك المتداولة في البورصة المصرية، والخروج بنتائج وتوصيات تخص موضوع البحث من خلال التعمق في دراسة الموضوع عن قرب بجانبيه النظري والعملي، حيث تم الاعتماد على بعض الأساليب الإحصائية لتحليل البيانات المتعلقة بالمشكلة محل البحث واختبار فروض الدراسة من خلال استخدام برنامجي SPSS و E-views للتحليل الإحصائي مع الاستعانة ببرنامج الاكسيل. توصلت هذه الدراسة إلى إنه يوجد تأثير طردي ذو دلالة إحصائية لمخاطر الائتمان على معدل العائد على الأصول ROA، ومعدل العائد على حقوق الملكية ROE، ونسبة مخصصات القروض غير المنتظمة PPL لدى البنوك التجارية في ضوء اتفاقية بازل 2، كما يوجد تأثير عكسي ذو دلالة إحصائية لمخاطر الائتمان على نسبة القروض غير المنتظمة NPL لدى البنوك التجارية في ضوء اتفاقية بازل 2.
This study aimed to find out the impact of credit risks (measured by the capital required to face Credit risks according to the Basel II standards) on the financial performance of the commercial banks (measured by profitability and asset quality), during a quarterly time series of eight years starting from the first quarter of 2013 until the fourth quarter of 2020 for a sample consisting of 7 banks trading in the Egyptian stock exchange; and to conclude the outcomes and recommendations related to the subject matter of the study by studying the subject theoretical and practical aspects closely. Some statistical methods were the basis to analyze the data related to the problem under research, and to test the hypotheses of the study through the use of the SPSS and E-views programs for statistical analysis with the help of Excel. This study concludes that there is a direct and statistically significant impact of credit risks on the rate of Return on Assets (ROA), the rate of Return on Equity (ROE), and the rate of the Provisions of Non-Performing Loans (PPL) with commercial banks in the light of the Basel II Accord, and there is also an adverse impact with a statistical significance for credit risks on the rate of Non-Performing Loans (NPL) of commercial banks in the light of the Basel II Accord.
Keywords: البنوك التجارية -- الأداء البنكي -- الأداء المالي -- المخاطر المصرفية -- المخاطر الائتمانية -- اتفاقية بازل 2